The Role of Organizational Commitment in Mediating The Influence of Work Motivation and Organizational Culture on Bappeda Provinsi Bali Employee Performance - Komang Yogi Lesmana; Anak Agung Media Martadiani; I Ketut Darma (Universitas Warmadewa, 2023)
The purpose of this study was to examine and analyze the effect of work motivation and organizational culture on employee performance through organizational commitment at BAPPEDA Provinsi Bali. This study uses a combination of quantitative and qualitative methods. The number of respondents in this case was 112 respondents. The collected data were analyzed using partial least square structural equation modeling (SEM-PLS). The results indicate that (1) work motivation influences employee performance, (2) organizational culture influences employee performance, (3) work motivation influences organizational commitment, (4) organizational culture influences organizational commitment, (5) organizational commitment influence on employee performance, (6) organizational commitment can partially mediate the effect of work motivation on employee performance, (7) organizational commitment can partially mediate the influence of organizational culture on employee performance.